The Regulation of Hunting: A Population Tax - Jens Abildtrup; Frank Jensen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
Within hunting, wildlife populations are estimated to be too high in many countries which is assumed to be due to the market failure, that each hunter harvests too little compared to what the regulator wants. This may be due to the existing regulation which, among other things, requires knowledge of the individual harvest. However, information about the individual harvest may be costly to obtain. Thus, we may have to look for alternatives to the existing system. This paper proposes a population tax/subsidy as an alternative which is the difference between the actual and optimal population multiplied by an individual, variable tax rate. The variable tax rate is, among other things, based on the difference in marginal value of the population between the hunter and the regulator. The paper shows that the population tax/subsidy secures a first-best optimum. Thus, the population tax is a good alternative to the existing regulation.
Keywords: 330